2016
DOI: 10.1117/12.2214229
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanowire gamma ray detector with high spatiotemporal resolution

Abstract: To my mom, Linda.iii ACKNOWLEDGEMENTSThere are no words to express how grateful I am for all the people that have been part of my life during this journey. I could not have completed my PhD without their help, and I would first like to thank the two advisors that guided me through my graduate career.Professor Richard Mu accepted me as an REU student during my final summer as an undergraduate. After interacting with his group and getting a chance to do actual research in a lab, I changed my graduate path from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Zinc oxide can also be used in high-temperature environments under high pressure due to its extremely high melting point of 1975 • C, since ZnO decomposes near the melting temperature at ambient pressure [4,5]. Moreover, ZnO has a high density of 5.61 g/cm 3 , which is less than that of conventional heavy-metal oxide scintillators but greater than that of plastic scintillators [6], resulting in a relatively low gamma-ray stopping power [7], and its fluorescence decay lifetime near ultraviolet exciton emission is only several hundreds of picoseconds [8]. Accordingly, ZnO is attractive for detecting high-energy rays and particles, such as X-rays, γ-rays, and α-particles with ultrafast response time in the environment with high radiation and high temperature [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide can also be used in high-temperature environments under high pressure due to its extremely high melting point of 1975 • C, since ZnO decomposes near the melting temperature at ambient pressure [4,5]. Moreover, ZnO has a high density of 5.61 g/cm 3 , which is less than that of conventional heavy-metal oxide scintillators but greater than that of plastic scintillators [6], resulting in a relatively low gamma-ray stopping power [7], and its fluorescence decay lifetime near ultraviolet exciton emission is only several hundreds of picoseconds [8]. Accordingly, ZnO is attractive for detecting high-energy rays and particles, such as X-rays, γ-rays, and α-particles with ultrafast response time in the environment with high radiation and high temperature [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO has good radiation hardness [2], however, due to its low density, its use in the registration of high-energy X-ray and gamma radiation can be restricted. Despite this, various authors have reported on ways to improve the spatial and temporal resolution of scintillators based on ZnO [3,4]. Successful application of a ZnO-based detector for the detection of nuclear radiation is reported in [5,6].…”
Section: Introductionmentioning
confidence: 99%